Peran Infrastruktur TI dalam Mendukung Sistem Informasi Kasir pada Rajo Coffee N Roastery - Fenny Purwani; Aulia Berliana Shanti; Awang Pramana Okta Rio; Dinda Ayu Ristianti (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
Information technology infrastructure is an important factor in supporting the effectiveness of cashier information systems, especially in food and beverage businesses that require fast, accurate, and structured transaction services. However, the use of a Point of Sale system still depends on the readiness of supporting infrastructure, such as devices, networks, data management, users, security, and operational procedures. Rajo Coffee N Roastery has implemented a cashier information system, but several potential problems remain, including internet dependency, limited cashier devices, input errors, account security, and the need for regular data backup. This study aims to identify the components of information technology infrastructure that support the cashier information system at Rajo Coffee N Roastery, explain the role of each component in transaction activities, analyze operational constraints, and formulate recommendations for system development. This research uses a descriptive qualitative approach with a case study method. Data were collected through literature review, direct observation of cashier activities, and informal interviews with parties involved in business operations. The data were analyzed using descriptive analysis and SWOT analysis to identify strengths, weaknesses, opportunities, and threats in the use of the cashier system. The results show that the cashier system is supported by an Android tablet, PUTIAN POS thermal printer, POS application, IndiHome Wi-Fi network, transaction data, cashier user, access security, and transaction procedures. These components help accelerate ordering, automate payment calculation, print receipts, and store sales data. The study recommends device maintenance, alternative networks, password protection, user guidelines, regular data backup, QRIS integration, stock management, cloud-based reporting, role-based access, and customer loyalty features.